Utilization of psychotropic medicines in Romania during 1998–2018 - Iaru, Irina; Bucsa, Camelia; Farcas, Andreea; Pop, Cristina; Cristina, Anamaria; Armean, Sebastian; Brumboiu, Irina; Vostinaru, Oliviu; Mogosan, Cristina (Frontiers in Pharmacology, 2023)
Background. Mental disorders can have a significant impact on patients’ life, including economic, social and individual consequences, and psychotropic medication is essential to treat these conditions. Psychotropic drug utilization studies contribute to a clearer picture of the management of these conditions. Data published from Romania on this topic is limited. The present study aims to characterize the utilization patterns of anxiolytics, antidepressants (Ads), and antipsychotics (Aps) in Romania during 1998-2018. Methods. Drug utilization data were provided by CEGEDIM Romania and quantitative data for each psychotropic medicine were converted to total defined daily doses (DDDs) and to DDD/1000inhabitants/day (DDD/TID). The total use of medicines in DDD/TID was computed in order to obtain the drug utilization 90% (DU90%) segment. Results. An increasing trend in total utilization of psychotropic medicines in Romania started in 2004. Anxiolytics use was predominant until 2013 and the yearly anxiolytic use over the entire study period remained between 10 and 15 DDD/TID. Diazepam lost popularity over time in detriment of the utilization of other anxiolytic benzodiazepines, such as alprazolam and lorazepam. ADs utilization markedly increased during the study period (the average annual growth rate was 13.66% starting 1999). SSRIs became present on the 2008 DU90% and was the dominant class of ADs, with sertraline being the most prescribed, followed by escitalopram and paroxetine. APs utilization showed an increasing trend from 2003 until 2018. Atypical APs became present on the 2008 DU90%, while typical APs were no longer included in the 2018 DU90%. Among atypical APs, olanzapine was the main agent prescribed, and starting 2010 was followed by quetiapine and risperidone. The uptake of APs long-acting formulations became more evident during the last analyzed years (2015-2018). Conclusions. We observed an increasing utilization of APs and a more prominent increase in ADs utilization in Romania during 1998-2018. The anxiolytic prescribing remained nearly stable during this time. Further research can bring more information on the various factors influencing psychotropic utilization in Romania.